A Review of Phosphate and Borate Sol–Gel Glasses for Biomedical Applications. Issue 3 (18th January 2021) - Lepry, William C.; Nazhat, Showan N.
Abstract : The sol–gel processing method revolutionizes the biomedical materials field, allowing for the customized creation of nano‐ and porous materials to help treat the toughest challenges in human health. However, this process and the subsequently produced materials have mostly been based on silica, particularly in terms of biomedical glasses. Yet, within the last two decades, there has been increased interest in silica‐free glass chemistries, such as those based on borate or phosphate. Attributable to their distinct properties which allows for linear and complete degradation, these glass compositions have shown great promise for both hard and soft tissue engineering applications, albeit with only a limited number of studies on glasses created through the sol–gel process. Therefore, this review provides an overview of the advancement of nonsilica sol–gel glasses, by focusing on borate and phosphate chemistries, for biomedical applications. A comprehensive review of these materials, including the challenges in processing as well as the current uses and future potential, is discussed. Abstract : Sol–gel borate and phosphate bioactive glasses are emerging as new biomaterials for a variety of applications due to their unique properties.